Psychosocial behavioral phenotypes of racially/ethnically minoritized older adults enrolled in HABS‐HD differ on neuroimaging measures of brain age gap, hippocampal volume, and cortical thickness - Alexandra L. Clark; Makenna B. McGill; Alexandra J. Weigand; Julie K. Wisch; Kalen Petersen; Beau Ances; Meredith N. Braskie; Sid O'Bryant; Kelsey R. Thomas; HABS‐HD Study Team (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION This study examined whether previously identified psychosocial behavioral phenotypes differed on structural neuroimaging markers. METHODS Latent profile analysis (LPA) employed in a sample of 1820 community‐dwelling older adults (1118 Hispanic and 702 Black) replicated previous Low Resource/Low Distress, High Resource/Low Distress, and Low Resource/High Distress phenotype classifications. Analyses of covariance (ANCOVAs) adjusting for relevant factors examined phenotype differences on neuroimaging outcomes of predicted brain age gap (BAG) (DeepBrainNet Predicted Age – Chronological Age), hippocampal volume, and cortical thickness of a meta‐temporal region of interest. RESULTS The Low Resource/Low Distress and Low Resource/High Distress phenotypes had significantly higher predicted BAGs relative to the High Resource/Low Distress phenotype, and the Low Resource/High Distress group displayed significantly lower hippocampal volumes and meta‐temporal cortical thickness relative to High Resource/Low Distress phenotype. DISCUSSION Results highlight there are neurostructural variations across psychosocial behavioral phenotypes and indicate the Low Resource/High Distress group may be at risk for ADRD. Highlights Brain age gap (BAG), hippocampal volumes, and cortical thickness differences were tested. The High Resource/Low Distress phenotype had the most favorable imaging outcomes. The Low Resource/High Distress phenotype demonstrated the poorest imaging outcomes. Risk for Alzheimer's disease and related dementias (ADRD) may differ across psychosocial behavioral phenotypes.